Rationale and Strategies for Socio-Political Legitimisation of Emerging Technologies elucidated on the Synthetic Biology Case - Princova, Diana (2016)
Emerging technologies face numerous social challenges and uncertainties that may hinder or prevent their development and diffusion. Success of controversial technologies like Synthetic Biology, in particular, relies heavily on their socio-political legitimacy (Hall et al., 2014). This paper first establishes a strong rationale for an adoption of socio-political legitimisation strategies through a discussion of significant communication and governance challenges of Synthetic Biology that were identified through interviews with various key stakeholders. Hereinafter, strategies for addressing these challenges are put forward, which would enable a smoother development and adoption of the technology. These strategies are also integrated to a framework of the socio-political legitimisation process, which explicates mutually reinforcing relationships among the proposed strategies and further establishes the rationale for adoption of legitimisation strategies.